The Application of STEM Learning to Improve Students’ STEM Literacy in The Knowledge Aspect - Harpian Harpian; Irma Rahma Suwarma; Andhy Setiawan (Journal of Innovation in Educational and Cultural Research, 2023)
STEM literacy is a competency that cannot be seen as knowledge of science, technology, engineering, and mathematics literacy separately. It is a competency consisting of content knowledge and an interdisciplinary skill component. This study aims to analyze students' STEM literacy after implementing STEM learning. The research method was quasi-experimental, and the research design used one group pretest posttest. The subjects of this study were 31 students of class XI IPA at a private high school in Bandung, Indonesia. The instrument in the study was 20 multiple-choice questions. The results showed that scientific literacy increased very satisfactorily (n-gain = 0.71) with an effect size of 1.36, technology-engineering literacy also increased very satisfactorily (n-gain = 0.72) with an effect size of 2.12 and mathematical literacy increased satisfactorily (n-gain = 057) with an effect size of 2.14. The research results show that students' STEM literacy is improved sufficiently and has a strong effect after implementing STEM learning. The study implies that STEM learning requires good collaboration between teachers to share information about students' constraints and solutions in working on project assignments.